2023
DOI: 10.1002/emp2.12943
|View full text |Cite
|
Sign up to set email alerts
|

Association between sex and survival after out‐of‐hospital cardiac arrest: A systematic review and meta‐analysis

Abstract: The current literature on sex differences in 30‐day survival following out‐of‐hospital cardiac arrest (OHCA) is conflicting, with 3 recent systematic reviews reporting opposing results. To address these contradictions, this systematic literature review and meta‐analysis aimed to synthesize the literature on sex differences in survival after OHCA by including only population‐based studies and through separate meta‐analyses of crude and adjusted effect estimates. MEDLINE and Embase databases were systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
1
1
0
Order By: Relevance
“…Our multivariable analysis findings, indicating no significant association between sex and survival outcomes, are consistent with the results of recent systematic reviews and meta‐analyses, 34 , 38 as well as other observational studies. 12 , 13 However, they are not in line with other studies suggesting an females have higher odds of survival, 23 , 39 and others indicating females have lower odds of survival.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our multivariable analysis findings, indicating no significant association between sex and survival outcomes, are consistent with the results of recent systematic reviews and meta‐analyses, 34 , 38 as well as other observational studies. 12 , 13 However, they are not in line with other studies suggesting an females have higher odds of survival, 23 , 39 and others indicating females have lower odds of survival.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, males experienced a higher incidence of OHCA in public locations and a greater proportion of witnessed arrests and shockable rhythms compared to females. Previous studies, including systematic reviews and meta‐analyses, 23,33–35 have consistently reported similar advantages in baseline characteristics for males. This may explain the higher crude survival rates observed in males.…”
Section: Discussionmentioning
confidence: 74%